2012
DOI: 10.3945/jn.111.154245
|View full text |Cite
|
Sign up to set email alerts
|

Vision Changes after Spaceflight Are Related to Alterations in Folate- and Vitamin B-12-Dependent One-Carbon Metabolism,

Abstract: Approximately 20% (7 of 38) of astronauts on International Space Station (ISS) missions have developed measurable ophthalmic changes after flight. This study was conducted to determine if the folate- and vitamin B-12-dependent 1-carbon metabolic pathway is altered in these individuals. Since 2006, we have conducted experiments on the ISS to evaluate nutritional status and related biochemical indices of astronauts before, during, and after flight. Data were modeled to evaluate differences between individuals wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(64 citation statements)
references
References 21 publications
(19 reference statements)
0
59
0
Order By: Relevance
“…For examples, higher serum Hcy levels and altered one-carbon metabolism have been reported in a subset of astronauts on the International Space Station who developed ophthalmic changes including altered NFL thickness, optic disc edema, globe flattening, choroidal folds, hyperopic shifts, and cotton wool spots. 44 There was no evidence of glaucoma or central retinal vein occlusion in the astronauts.…”
Section: Discussionmentioning
confidence: 90%
“…For examples, higher serum Hcy levels and altered one-carbon metabolism have been reported in a subset of astronauts on the International Space Station who developed ophthalmic changes including altered NFL thickness, optic disc edema, globe flattening, choroidal folds, hyperopic shifts, and cotton wool spots. 44 There was no evidence of glaucoma or central retinal vein occlusion in the astronauts.…”
Section: Discussionmentioning
confidence: 90%
“…[27][28][29][30] 14 Vitamin B 12 or folate deficiencies, even those that are detected by screening of asymptomatic populations, can cause optic neuropathies such as optic disc swelling and vision impairment.…”
Section: Optic Neuropathy and B Vitaminsmentioning
confidence: 99%
“…• Cataract incidence is increased by space flight, secondary to radiation and oxygen exposure, Table 1 in Zwart et al (2012). • Cataract incidence is increased by space flight, secondary to radiation and oxygen exposure, Table 1 in Zwart et al (2012).…”
Section: Take-home Messagesmentioning
confidence: 99%
“…[75][76][77] Recently, very important clinical findings have emerged from studies of visual function during and after long-term spaceflight. 79 The biochemical differences observed in crew members with visual deficits strongly suggest that folate-and vitamin B 12 -dependent one-carbon transfer metabolism was affected before and during flight. 78 The cause of the ophthalmic changes is not known, but the initial report suggested that perhaps microgravity-induced cephalad fluid shifts or localized intraorbital changes were involved.…”
Section: In Vitro and In Vivo Studies Of Hyerhomocysteinemia And The mentioning
confidence: 99%